106 minima timings of eclipsing binaries - Karampotsiou, E.; Gazeas, K.; Petropoulou, M.; Tzouganatos, L. (Information Bulletin on Variable Stars, 2016)
We present 106 times of minima of 27 eclipsing binaries.
Keywords: CCD photometry